sqrt(6+x)*sqrt(4-x)=3

Simple and best practice solution for sqrt(6+x)*sqrt(4-x)=3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for sqrt(6+x)*sqrt(4-x)=3 equation:


Simplifying
sqrt(6 + x) * sqrt(4 + -1x) = 3

Reorder the terms for easier multiplication:
qrst * qrst(6 + x)(4 + -1x) = 3

Multiply qrst * qrst
q2r2s2t2(6 + x)(4 + -1x) = 3

Multiply (6 + x) * (4 + -1x)
q2r2s2t2(6(4 + -1x) + x(4 + -1x)) = 3
q2r2s2t2((4 * 6 + -1x * 6) + x(4 + -1x)) = 3
q2r2s2t2((24 + -6x) + x(4 + -1x)) = 3
q2r2s2t2(24 + -6x + (4 * x + -1x * x)) = 3
q2r2s2t2(24 + -6x + (4x + -1x2)) = 3

Combine like terms: -6x + 4x = -2x
q2r2s2t2(24 + -2x + -1x2) = 3
(24 * q2r2s2t2 + -2x * q2r2s2t2 + -1x2 * q2r2s2t2) = 3
(24q2r2s2t2 + -2q2r2s2t2x + -1q2r2s2t2x2) = 3

Solving
24q2r2s2t2 + -2q2r2s2t2x + -1q2r2s2t2x2 = 3

Solving for variable 'q'.

Move all terms containing q to the left, all other terms to the right.

Reorder the terms:
-3 + 24q2r2s2t2 + -2q2r2s2t2x + -1q2r2s2t2x2 = 3 + -3

Combine like terms: 3 + -3 = 0
-3 + 24q2r2s2t2 + -2q2r2s2t2x + -1q2r2s2t2x2 = 0

The solution to this equation could not be determined.

See similar equations:

| 10+-2z=-30 | | 11x-5=60 | | 5m-4=3m+12 | | w^3+5w^2+-23w-3= | | -2=-9-2(-2x+1) | | -7f+-31=53 | | X^3-2x+21=0 | | 20+-10c=100 | | 2b+a=5 | | 2,711/9= | | 0.9=0.8+x-0.8x | | (-4x)(-2x^2)= | | x-21=2x+3 | | (w-3)(w^2+8w+1)= | | 7(x+6)=8(x-4) | | t^2+48t=0 | | (4x)=26 | | 7n^7+9n+5= | | 10.4+4= | | -x^2-12-18=0 | | 10/x=25/20 | | 9(s+10)+7=3s-11 | | f(x)=-2-2x | | rainbow+7=fun | | (n+1)(n^2+4n+5)= | | 2y+4=3-4+5y | | 16x-5+91=180 | | -28=6(2c-7) | | 100+8x+8=180 | | 5k^2+10=90 | | 4x+14=-58 | | p/4plus13=21 |

Equations solver categories